👤
a fost răspuns

(2/5√3-1/√12+3/√75)·√27

Răspuns :

[tex]( \frac{2}{5 \sqrt{3} } - \frac{1}{ \sqrt{12} } + \frac{3}{ \sqrt{75} } ) \times \sqrt{27} [/tex]

[tex] = ( \frac{2}{5 \sqrt{3} } - \frac{1}{2 \sqrt{3} } + \frac{3}{5 \sqrt{3} } ) \times 3 \sqrt{3} [/tex]

[tex] = ( \frac{2}{5} - \frac{1}{2} + \frac{3}{5} ) \times 3[/tex]

[tex] = ( \frac{4}{10} - \frac{5}{10} + \frac{6}{10} ) \times 3[/tex]

[tex] = \frac{4 - 5 + 6}{10} \times 3[/tex]

[tex] = \frac{1}{10} \times 3[/tex]

[tex] = \frac{1 \times 3}{10} [/tex]

[tex] = \frac{3}{10} [/tex]